(untitled) (Orfeu, 2020)
This article deals with a proposal in the field of music theory through analogy between phraseology of music and poetic elaboration. The methodology starts from the themes of the historical treatises on music phraseology and philosophical themes on poetry. As a result, through an analytical practice and coping with phraseology with poetic rules, one came to a proposal of two new phraseology categories. Concluding, the phraseology of music structures of the songs in the Brazilian popular music repertoire could be understood as analogous to certain poetic structures, thus, leading to conceptual discussions derived from the problem presented.